The Physician’s Task and the Problem of Documentation - Proppe, A. (Methods of Information in Medicine, 1964)
Case histories suitable for statistical evaluation can be found even as far back as in the Corpus Hippocraticum. Such simple data as the patient’s age, body weight, size, the date of menarche, etc. are practically always included in the case records, and it is demonstrated that, when such data are recorded in a system of documentation suitable for mechanical sorting, it may enable us to draw conclusions of very great importance. Mechanical registration methods have revealed that, in the determination and recording of data as hitherto carried out. there has been a surprisingly large number of errors and a high degree of unreliability. This view has a considerable influence on modern clinical methods; it renders a more democratic relation between physician and patient necessary and makes clear the need for measures to enhance the reliability of diagnosis and treatment of pathological conditions. The author illustrates this view with reference to the mechanical falsification of the thesis of the proneness of early age groups to lupus vulgaris, furthermore with reference to the mechanical rationalization of modern routine diagnostic methods, to the constant surveillance of adverse effects on public health and to the protection against allergic reactions with the aid of recording systems of personal allergy and intolerance data with mechanical sorting and computer techniques.